Metalloproteinases in non-alcoholic fatty liver disease and their behavior in liver fibrosis - Barchuk, Magalí (2018)
Non-alcoholic fatty liver disease (NAFLD) is a clinical entity of high prevalence in the world characterized by fatty infiltration of liver tissue in the absence of alcohol consumption. The natural history of the disease develops in successive phases reflected in different histological stages, with 10-20% of patients developing liver cirrhosis and fibrosis. Fibrosis is a basic connective tissue lesion defined by the increase of the fibrillary extracellular matrix (ECM) components in a tissue or organ. Matrix metalloproteinases (MMPs) constitute a family of endopeptidases, which are involved in ECM and basement membranes components degradation. Fibrogenic process is characterized by altered ECM composition, associated with modifications in MMPs behavior. The active cross-talk between adipose tissue and liver can be altered in pathologies associated to insulin resistance (IR), such as NAFLD. The role of adipokines on MMPs behavior in the liver could be partly responsible of liver damage during IR. The aim of this revision is to describe the behavior of MMPs in NAFLD and its role in the associated fibrosis.